PENGARUH PENGUNGKAPAN SUKARELA MANAJEMEN RISIKO NON-KEUANGAN TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Sektor Energy yang Terdaftar di Bursa Efek Indonesia pada Tahun 2020) - Yosua Andhar; Paulus Th. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2023)
This study aims to examine the effect of voluntary risk management disclosure on firm value in the Energy sector listed on the Indonesia Stock Exchange (IDX) for the 2020 period. In addition, this study also examines more complete and broad disclosures from companies are able to minimize information asymmetry for investors in making investment decisions. Based on signal theory, which is related to information asymmetry, companies that disclose more information will have high firm value as well. The population in this study were companies in the Energy sector for the 2019 period with a total sample of 60 out of 67 populations listed on the Indonesia Stock Exchange (IDX). This study uses multiple regression analysis as an analytical tool. The results showed that the voluntary disclosure of strategic risk management and information technology processing risk management had a positive and significant effect on firm value. Meanwhile, voluntary disclosure of operating risk management, integrity risk management and empowerment risk management has no effect on firm value. Based on these results, it can be said that wider voluntary risk management disclosure of strategic risk management and information technology processing risk management will increase the value of the company in the investor's perspective, while the ineffectiveness of voluntary disclosure of operating risk management, integrity risk management and empowerment risk management may be influenced by several other factors.